Redesign Facility Layout With Quantitative And Qualitative Method On Printing Industry - Trifenaus Prabu Hidayat; Andre Sugioko; Gabriella Ratna Widiastuti (Fakultas Teknik, Universitas Katolik Widya Mandala Surabaya, 2016)
Performance and productivity production line system are very influenced by facility layout planning. Facilities composition if appropriate with flow of materials between departments, it will sustain the continuity of the system. PT. X engaged in the field of printing. Composition of the current layout facilities on the Plant has not fully optimized well and indeed has a potential possibility to be developed further in the future. This statement is supported from the result of existing MHPS which gives Rp 6.560.374,50 for total cost of material handling and 136329 metres for total distance. As for the purposes of this research are: evaluating the performance of current facility layout, designing the layout of the facility with qualitative and quantitative methods, comparing the current with proposed improvement layouts, as well as create a picture the new layout facility. The process of designing proposed layouts is done by using qualitative methods (CORELAP, BLOCPLAN & CRAFT) and quantitative methods (ABSMODEL & CRAFT) that both of the algorithms need same inputs, which are: current facility layout and the flow of material. Based from the results of calculation proposed layouts, show that layout from qualitative methods (CORELAP) gives maximal reduction to the total cost of material handling so that the amounts will be decreased to Rp 6.100.133,55 (reducing 7,02% from total cost of current layout), and 117264 metres for total distance (reducing 13,985%.). Kata kunci : facility layout, quantitative methods, qualitative methods